Model Analysis of Civil Servant Requirement in the Human Resources Development Agency (BKPSDM) of Balikpapan City - Hadijaya, Isman; Anggraeni, Rinny Dwi (Institut Pemerintahan Dalam Negeri, 2023)
At present, there is an ongoing assessment of competency development requirements at the organizational level within the Balikpapan City BKPSDM unit. The findings of this examination delve into the necessity for competency development at the organizational level, scrutinizing the challenges and future issues faced by BKPSDM. The analysis involves the meticulous collection of data and information pertaining to the unit's challenges. These findings serve as a foundation for evaluating the individual competency development needs of each employee based on their respective roles. To enhance the professionalism of civil servants (ASN), the government must implement strategies such as aligning Civil Servants with their respective fields of expertise to maximize productivity. Furthermore, it is imperative for the government to uphold a conducive organizational environment to mitigate external influences on ASNs. A transparent and effective recruitment system, currently operating on a merit basis, is essential. However, relying solely on the merit system is insufficient; individuals must demonstrate a willingness to embrace change and take on responsibilities with dedication. The proposed model for competent state civil servants at Balikpapan City BKPSDM is the Quantum Leadership Model, encompassing five key follower roles: strategic implementor, follower as the leader, source of information, feedback provider, and friends and partners. These roles emphasize the multifaceted responsibilities of civil servants in executing strategic initiatives, showcasing leadership qualities, providing information, offering feedback, and fostering collaborative relationships. Additionally, meeting the demands for transparency in governance underscores the need to reinforce public relations and work relations, especially in the face of global competition.